2013
DOI: 10.1104/pp.113.218644
|View full text |Cite
|
Sign up to set email alerts
|

A Chloroplast ABC1-like Kinase Regulates Vitamin E Metabolism in Arabidopsis      

Abstract: In bacteria and mitochondria, ABC1 (for Activity of bc1 complex)-like kinases regulate ubiquinone synthesis, mutations causing severe respiration defects, including neurological disorders in humans. Little is known about plant ABC1-like kinases; in Arabidopsis (Arabidopsis thaliana), five are predicted in mitochondria but, surprisingly, six are located at lipid droplets in chloroplasts. These are a known site of prenylquinone (including tocopherol [vitamin E], phylloquinone [vitamin K] and plastoquinone) metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 38 publications
6
93
0
6
Order By: Relevance
“…This supports the idea that the accumulation of DMPBQ under HL is not sufficient to completely replace a-tocopherol and assume its membrane protective role in the thylakoid membranes [2,44,45]. vte2 displayed a simi-lar phenotype under short-term HL stress as vte1 [2].…”
Section: Current Opinion In Plant Biologysupporting
confidence: 71%
See 2 more Smart Citations
“…This supports the idea that the accumulation of DMPBQ under HL is not sufficient to completely replace a-tocopherol and assume its membrane protective role in the thylakoid membranes [2,44,45]. vte2 displayed a simi-lar phenotype under short-term HL stress as vte1 [2].…”
Section: Current Opinion In Plant Biologysupporting
confidence: 71%
“…At the protein level, however, Martinis et al [44,48 ] showed significantly lower contents of VTE1 in the abc1k1/pgr6 and abc1k3 mutants than in wt. These data suggest that ABC1K1/ PGR6 and ABC1-K3 stabilize VTE1 levels.…”
Section: Current Opinion In Plant Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…The Atabc1k7 mutant developed larger plastoglobules and lipid composition of the chloroplast membrane when compared with wide-type Arabidopsis (Manara et al, 2014(Manara et al, , 2015. Additionally, ABC1K1/3, as a complex, binds with phosphorylated tocopherol cyclase to affect plastoquinone metabolism (Lundquist et al, 2013;Martinis et al, 2013Martinis et al, , 2014Manara et al, 2014). Their double mutation also leads to abnormal accumulation of plastoglobules in Arabidopsis.…”
Section: Plastoglobule Composition and Formation Within Citrus Flesh mentioning
confidence: 99%
“…It would be interesting to test whether other stress situations also allow PC-8 accumulation and to distinguish the relevant regulatory mechanisms. In Arabidopsis, PC-8 levels are regulated by the activity of a type II NADPH dehydrogenase C1 (ortholog is NDA5 in Chlamydomonas) (47,48) and a plastid ABC1-like kinase (49).…”
mentioning
confidence: 99%